[LB.03.05] HELPER-DEPENDENT ADENOVIRUS-MEDIATED GENE TRANSFER OF A SECRETED LDL RECEPTOR/TRANSFERRIN CHIMERIC PROTEIN REDUCES AORTIC ATHEROSCLEROSIS IN LDL RECEPTOR-DEFICIENT MICE. (September 2017) - Leggiero, E.; Labruna, G.; Iaffaldano, L.; Lombardo, B.; Tripodi, L.; Greco, A.; Fiorenza, D.; Gramanzini, M.; Salvatore, F.; Sacchetti, L.; Pastore, L.
Abstract : Objective: Familial hypercholesterolemia is a genetic hyperlipidemia characterized by elevated concentration of plasma LDL cholesterol. Statins are not effective in all patients whose prognosis is still quite poor. In the past, we have developed safe and effective gene therapy strategies for the expression of anti-atherogenic proteins using PEGylated helper-dependent adenoviral (HD-Ad) vectors. We recently developed a HD-Ad vector for the expression of a secreted chimeric protein containing the extracellular portion of the human LDL receptor (LDLR) fused with a transferrin dimer. These project would represent a constitute proof of concept of the possibility of lowering LDL-C and reducing atherosclerosis using a secreted transgene and an alternative intracellular route. Design and method: Development of an HD-Ad vector for liver-directed expression of the TF-LDLR, a fusion protein that mimicks the function of the LDLR; Evaluation of the effect of the TF-LDLR fusion protein in the FH cellular model and mouse model Assessment of efficacy of the PEGylated HD-Ad vector expressing TF-LDLR Evaluation of alternative administration routes for the PEGylated HD-Ad vector expressing TF-LDLR fusion protein. Results: We evaluated the efficacy of vector in CHOldla7 cell line, in which we restored the cell ability to uptake of labeled LDL. We administered intravenously 1X10E13 vp/kg of the HD-Ad vector expressing TF-LDLR in LDLR-deficient mice demonstrating the efficacy of the vector in reducing total and LDL cholesterol levels;in addition, expression of TF-LDLR significantly reduced aortic atherosclerotic lesions in treated LDLR-deficient mice compared to controls. Moreover, we administered in VivoTag 750S-Labeled LDL to study biodistribution in LDLR-deficient mice treated with either HD-Ad TF-LDLR or control vector and we found a strong signal in the heart, liver and intestin after Fluorescence molecular tomography analysis. Conclusions: We demonstrated: In vitro expression and efficacy of the TF-LDLR fusion protein; HD-Ad-mediated in vivo expression of TF-LDLR; Improvement of lipid profile in LDLR-deficient mice treated with TF-LDLR. Reduction of aortic atherosclerosis lesions size in LDLR-deficient mice treated with TF-LDLR. Future steps of our project will involve a thorough safety evaluation of our approach and the possibility of administering the HD-Ad vector in its PEGylated version using alternative routes.